Perlindungan Hukum Bagi Konsumen Perumahan Terhadap Promosi Yang Tidak Sesuai Dengan Yang Diperjanjikan Sesuai Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Nini Saputri; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Consumer protection is any effort that ensures the legal certainty to provide protection to the consumer. One of the ideals of the struggle of the Indonesian nation is the realization of a just and prosperous society based on Pancasila and the 1945 Constitution in line with national development objectives is to realize the welfare of the birth and the inner for all the people of Indonesia in a fair and equitable. One of the basic elements of people's welfare is the fulfillment of housing needs, which is a basic necessity for every Indonesian citizen and his family, in accordance with his dignity and human dignity. To meet the needs of good and livable housing, people buy homes through developers (developers) housing. Various offers are made by the developer to promote and market their products. In general, residential marketing is done by means of advertising means or brochures as a means of communicating products created and / or marketed by the developer to introduce or disseminate information from the product that the developer has created. The advertisement through the brochure, as well as to attract consumers to buy products in the trade, in this case is housing.namun still many developers are cheating in offering products through brochures not in accordance with the truth, this is clearly violate the Consumer Protection Act namely Law No. 8 of 1999 on Consumer Protection and violated Article 134 of Law No. 1 of 2011 on Housing and Settlement Area. The purpose of this thesis writing so that Consumers are more careful and thorough in buying housing that will in hini, as well as warning for housing developers who have violated the rights of consumers. This type of research can be classified in sociological research, because in this study the authors directly conduct research on the location or place in the meticulous to provide a complete and clear picture of the problem under study. This research was conducted on Tuah Tualang housing of siak district, while for population and sample are all parties related to the problem studied in this research,From the results of this study it can be concluded that there are still many cases in the Consumer Protection Law which in this case the most disadvantaged consumers, especially on consumer protection concerning housing whose bidding system is made by the developer through brochures or advertisements that in fact are not in accordance with the contents which is in the brochure.Suggestions are expected to consumers to be more careful in buying a house on the developers because of the rampant housing cases that occur,Keywords: wanprestasi - consumer protection - housing